Effect of 4MAT Learning Strategy on Students’ Performance in Animal and Crop Breeding in North-East Nigerian Universities - Barka; Abubakar; Maryam; Victor (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study investigated the effectiveness of the 4MAT learning strategy on the academic performance of agricultural education students in animals and crops breeding in North-East Nigerian universities. The study adopted a quasi-experimental design involving 106 of 300-level undergraduate students from two purposively selected universities. Data were collected using the Animals and Crops Breeding Cognitive Performance Test (ACBCPT). Pre-test and post-test scores were analyzed using descriptive statistics and Analysis of Variance (ANOVA) to determine differences between the experimental 4MAT group and the control group taught using conventional methods. The study found that the 4MAT learning strategy significantly improved students’ academic performance in the post-test, while pre-test scores showed no significant difference, indicating equivalence at the baseline. The instruments used were valid and reliable, with Cronbach alpha coefficients above the recommended thresholds. The findings suggest that learner-centered, innovative teaching strategies enhance understanding, engagement, and mastery of complex agricultural concepts.
Keywords: Agricultural Education; Animal and Crop breeding; 4MAT Learning Strategy; Academic performance; Quasi-Experimental Design; North-east Nigeria